The public transport choices: UUM experiences - Mohd Seman, Nor Suhada; Sabar, Rohafiz (2012)
The purpose of this research generally is to find the relationship of the public transport services among student. The research was conduct using journal and articles and also using survey by distributing the questionnaire to the respondent. A total of 100 respondents of UUM students who were selected by sampling. The public transport service is a vital to University operation. Students should choose the public transport services that meet the price, safety and give the beneficial for them to ensure their satisfaction. The conclusions that can be made are the entire student has a direct relationship with public transport services. The terms of gender and ability also have a direct relationship with the transport services.